Expansion and socio-environmental impacts of the culture of Eucalyptus spp. (Myrtaceae) in Brazil: a literature panorama (Research, Society and Development, 2022)
In Brazil Eucalyptus has been a very cultivated genus because it has desirable commercial characteristics, considering that cellulose, wood and essential oils are used in most species. Thus, this study aimed to compile data on the expansion of eucalyptus culture in Brazil in the last decade and its socio-environmental impacts. A literature review was carried out by consulting books and scientific articles from the electronic databases Scielo, Periodicals CAPES and EBSCO Discovery Service (EDS). Over the last 20 years, the demand from the foreign market has positioned Brazil at high levels in the world context of pulp production and has led to a great expansion of the eucalyptus planted area in Brazil in the last decade. The activities of the implantation, maintenance and harvesting phases of the eucalyptus crop, result in changes in the socio-environmental conditions that used to exist in the place. Among the beneficial impacts is the positive contribution to the national economy, as it generates an increase in trade, with products for domestic consumption and for export, taxes and jobs for the population. Among the adverse impacts are the impoverishment of local biodiversity, environmental degradation and conflicts in rural and urban areas. To minimize these adverse impacts, it is necessary to implement ecologically correct environmental management, with the identification of local environmental conservation characteristics and conditions (such as proximity to riparian vegetation areas, local biodiversity, types of climate and soil, terrain slope, water availability in the hydrographic basin), the pre-existing land structure and implementation of a set of mitigating actions for each adverse impact.